The Effect of socialization and professionalism of amil towards muzakki's motivation to pay zakat (case study of Baitul Mal Aceh Tamiang Regency) - Kurniasih, Cut Endang; Anggraini, Fina (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2022)
Purpose – The main objective of this study is to examine whether the socialization and professionalism of amil affect the motivation of muzakki to pay zakat at Baitul Mal in Aceh Tamiang, either partially or simultaneously. Methodology – This study applies multiple regression analysis and classical assumption test to handle the primary and secondary data to examine the effect of socialization and professionalism of amil on muzakki's motivation. It also uses cluster random sampling to decide the possible samples to be interviewed. Findings – The results show that socialization partially has a positive and insignificant effect on the motivation of muzakki to pay zakat. But partially amil professionalism has a significant positive effect on muzakki's motivation to pay zakat at Baitul Mal Aceh Tamiang. Overall, the socialization and professionalism of amil simultaneously have a significant effect on the motivation of muzakki to pay zakat. Based on the R2 test, 22.9% socialization and professionalism of amil affect the motivation of muzakki who pay zakat in Baitul Mal Aceh Tamiang, while 77.1% is explained by other factors. Limitation – Despite the author's efforts, data on a number of variables, are collected by questionnaire instruments only at Baitul Mal in Aceh Tamiang. Therefore, further studies may collect data on another location and apply different approach to examine their impact on the muzakki's motivation. Practical Implication – Zakat institution has important implications for encouraging the socialization strategy and professionalism of amil to be able to create a mindset of the community in order to create motivation to pay zakat through Baitul Mal.